Predicting technology utilisation of learning management system among Malaysian polytechnic students - Ismail, Norhafizah (2017)
The major purpose of the current study is to identify the predicting factors, mediators and moderators towards effective technology use of Curriculum Information Document Online System (CIDOS) Learning Management System (LMS) among full-time undergraduate diploma students of Engineering Department at Malaysian Polytechnics. The theories underpinning this study are Theory Reasoned Action (TRA), Technology Acceptance Model (TAM), Substitution, Augmentation, Modification and Redefinition (SAMR) model and Adaptive Structuration Theory (AST). There are six predicting factors involved; compatibility, application selfefficacy, subjective norm, technological complexity, perceived usefulness and perceived ease of use. Technology utilisation is a dependent variable which encompasses of consistency of use, as well as quality of use. Genders and level of integration are the moderators, meanwhile perceived usefulness and perceive ease of use are classified as mediators. A pilot test was implemented on 100 undergraduate technical students of Politeknik Merlimau, Melaka (PMM) to measure the research instrument’s reliability. The value of Cronbach’ s alpha obtained ranged from 0.828 to 0.933. For the measurement model, Confirmatory Factor Analysis (CFA) was required to test the consistency of construct and determine construct validity. The present study was carried out on 372 second-year students from five polytechnics of Malaysia (Premier and Conventional) including Politeknik Ungku Omar (PUO), Politeknik Sultan Salahuddin Abdul Aziz Shah (PSA), Politeknik Merlimau, Melaka (PMM), Politeknik Ibrahim Sultan (PIS) and Politeknik Port Dickson (PPD). The sampling technique used was two-stage cluster sampling. The quantitative method with descriptive research was conducted by analysing the statistics of mean, standard deviation, percentage and frequency. The statistical analysis of Structural Equation Modelling (SEM), using AMOS Version 22, was utilised. Based on the measurement model testing, among the 10 paths, 9 were significant and only one was not. The 10 paths were: 1) compatibility positively effects perceived usefulness (β=.516, p<0.001); 2) application self-efficacy has no a significant effect on perceived usefulness (β=.105, p>0.05); 3) subjective norm positively effects perceived usefulness (β=.143, p<0.05); 4) technological complexity negatively effects perceived usefulness (β=-.165, p<0.01); 5) compatibility positively effects perceived ease of use (β=.322, p<0.001); 6) application self-efficacy positively effects perceived ease of use (β=.344, p<0.001); 7) subjective norm positively effects perceived ease of use (β=.158, p<0.01); 8) technological complexity negatively effects perceived ease of use (β=-.214, p<0.001); 9) perceived usefulness positively effects technology utilisation (β=.265, p<0.001); and 10) perceived ease of use positively effects technology utilisation (β=.343, p<0.001). Based on the revised structural model, the main contribution for PU and PEOU was pertained to compatibility (β=.516, p<.001; β=.322, p<.001). The outcome of evaluation conceded that predictors TU could explain 67.7% of its variance. In the interim, the leading contribution was ASE (β=.344, p<.001) and followed by PEOU (β=.343, p<.001). The mediation test findings also revealed that among eight mediation tests, six were not supported (no mediation), and two met full mediation. The findings of mediation test revealed that PU does not mediate the influence of C on PU; PU does not mediate the influence of ASE on TU; PU does not mediate the influence of SN on TU; PU does not mediate the influence of TC on TU; PEOU does not mediate the influence of C on TU; PEOU does mediate the influence of ASE on TU; PEOU does not mediate the influence of SN on TU and PEOU does mediate the influence of TC on TU. ASE fully mediates the influence of PEOU on TU and TC fully mediates the influence of PEOU on TU. Gender fully moderates the relationship between PU and TU since the standardized estimates for male is significant and female is not significant. Level of integration partially moderates the relationship PEOU and TU since the standardized estimates for Semester 3 and 4 are both significant.